Refractory cor pulmonale under extracorporeal membrane oxygenation for acute respiratory distress syndrome: the role of conversion to veno-pulmonary arterial assist—a case series - Bagate, François; Masi, Paul; Boukantar, Madjid; Radu, Costin; Saiydoun, Gabriel; Fiore, Antonio; Chiaroni, Paul-Matthieu; Teiger, Emmanuel; Folliguet, Thierry; Gallet, Romain; Mekontso Dessap, Armand (Frontiers in Medicine, 2024)
Introduction Pulmonary vascular dysfunction during severe acute respiratory distress syndrome (ARDS) may lead to right ventricle (RV) dysfunction and acute cor pulmonale (ACP). The occurrence/persistence of ACP despite conventional extracorporeal membrane oxygenation (ECMO) is a challenging situation. We explored the usefulness of a specific dual-lumen cannula that bypasses the RV, and on which a veno-pulmonary arterial assist (V-P ECMO) was mounted, in ARDS patients. Methods We report a case-series of ARDS patients put on conventional veno-arterial or veno-venous ECMO and presented refractory ACP as an indication for a reconfiguration to V-P ECMO using the ProtekDuo cannula. The primary endpoint was the mitigation of RV and pulmonary vascular dysfunction as assessed by the change in end-diastolic RV/left ventricle (LV) surface ratio. Results Six patients had their conventional ECMO reconfigured to V-P ECMO to treat refractory ACP. There was a decrease in end-diastolic RV/LV surface ratio, as well as end-systolic LV eccentricity index, and lactatemia immediately after V-P ECMO initiation. The resolution of refractory ACP was immediately achieved in four of our six (66%) patients. The V-P ECMO was weaned after a median of 26 [8–93] days after implantation. All but one patient were discharged home. We detected one case of severe hemolysis with V-P ECMO and two suspected cases of right-sided infective endocarditis. Conclusion V-P ECMO is useful to mitigate RV overload and to improve hemodynamics in case of refractory ACP despite conventional ECMO.